1992
DOI: 10.1093/mutage/7.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Development of assays for the detection of photomutagenicity of chemicals during exposure to UV light. II. Results of testing three sunscreen ingredients

Abstract: Three sunscreen ingredients, derivatives of benzylidene camphor, were tested for photomutagenic potential. These were benzenesulfonic acid, 4-[(4,7,7,-trimethyl-3-oxo-bicyclo [2.2.1] hept-2-ylidene) methyl] (Mexoryl SL), 4-(2-oxo 3-bornylidenemethyl) phenyl trimethylammonium methyl sulphate (Mexoryl SO) and 3,3'-(1,4-phenylenedimethylidyne) bis [7,7-dimethyl-2-oxo-bicyclo [2.2.1] heptane-1-methanesulfonic acid] (Mexoryl SX). Two complementary assay systems were used, one involving the induction of reverse muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…For the positive control, in the presence of 10 g/plate of 8-MOP, the number of revertant bacteria colonies for TA102 increases steadily as the light dose increases before reaching a maximum number of about six times the revertant colonies of the spontaneous mutation. This result is comparable to the literature values [12][13][14][15].…”
Section: Photomutagenicity Assaysupporting
confidence: 91%
See 1 more Smart Citation
“…For the positive control, in the presence of 10 g/plate of 8-MOP, the number of revertant bacteria colonies for TA102 increases steadily as the light dose increases before reaching a maximum number of about six times the revertant colonies of the spontaneous mutation. This result is comparable to the literature values [12][13][14][15].…”
Section: Photomutagenicity Assaysupporting
confidence: 91%
“…Several European communities have recently published guidelines for testing chemicals with regard to photomutagenicity [12][13][14][15]. Although ideal photomutagenicity assay is to use the level of light only to photo-activate the chemicals that results in mutation, not to cause death of the bacteria.…”
Section: Photomutagenicity Assaymentioning
confidence: 99%
“…To avoid damage caused by prolonged exposure to the sun, the effective utilization of sunscreen should be further encouraged. On the other hand, Xu and Parsons have reported the cytotoxic effect of a sunscreen component in cultured human cells [29], although Dean et al showed no photomutagenicity of three sunscreen ingredients with UV light using bacterial reverse mutation and a mammalian chromosome aberration assay [30]. The Drosophila systems used in this study could also be used to examine the genotoxicity of the sunscreen itself, with an investigation of the effects of direct contact of sunscreen with larvae being one approach.…”
Section: Discussionmentioning
confidence: 83%
“…7,8,[10][11][12][13][14][15][16][17][18] Skin Pigmentation E x p o s u re to solar UV irradiation generally causes increased pigmentation of the skin, known as tanning, as a result of increased melanin production. UVA radiation, in particular, plays a major role in the induction of longlasting pigmentation, which may persist from several months to 1 year.…”
Section: Efficacy Of Compoundsmentioning
confidence: 99%
“…Numerous in vitro and in vivo studies with Mexoryl SX and Mexoryl XL have demonstrated their efficacy in the prevention of UV radiation–induced damage, including skin pigmentation, photoaging, and skin photosensitivity reactions. 7,8,1018…”
Section: Efficacy Of Compoundsmentioning
confidence: 99%